Time dependent risk of gastrointestinal complications induced by non-steroidal anti-inflammatory drug use: a consensus statement using a meta-analytic approach. Issue 7 (11th June 2004) - Richy, F; Bruyere, O; Ethgen, O; Rabenda, V; Bouvenot, G; Audran, M; Herrero-Beaumont, G; Moore, A; Eliakim, R; Haim, M; Reginster, J-Y
Abstract : Objectives: To provide an updated document assessing the global, NSAID-specific, and time dependent risk of gastrointestinal (GI) complications through meta-analyses of high quality studies. Methods: An exhaustive systematic search was performed. Inclusion criteria were: RCT or controlled study, duration of 5 days at least, inactive control, assessment of minor or major NSAID adverse effects, publication range January 1985 to January 2003. The publications retrieved were assessed during a specifically dedicated WHO meeting including leading experts in all related fields. Statistics were performed conservatively. Meta-regression was performed by regressing NSAID adjusted estimates against study duration categories. Results: Among RCT data, indolic derivates provided a significantly higher risk of GI complications related to NSAID use than for non-users: RR = 2.25 (1.00; 5.08) than did other compounds: naproxen: RR = 1.83 (1.25; 2.68); diclofenac: RR = 1.73 (1.21; 2.46); piroxicam: RR = 1.66 (1.14; 2.44); tenoxicam: RR = 1.43 (0.40; 5.14); meloxicam: RR = 1.24 (0.98; 1.56), and ibuprofen: RR = 1.19 (0.93; 1.54). Indometacin users had a maximum relative risk for complication at 14 days. The other compounds presented a better profile, with a maximum risk at 50 days. Significant additional risk factors included age, dose, and underlying disease. The controlled cohort studies provided higher estimates: RR =  2.22 (1.7; 2.9). Publication bias testing was significant, towards a selective publication of deleterious effects of NSAIDs from small sized studies. Conclusion: This meta-analysis characterised the "compound" and "time" aspects of the GI toxicity of non-selective NSAIDs. The risk/benefit ratio of such compounds should thus be carefully and individually evaluated at the start of long term treatment.